Value Based Scout Management in Shaping Elementary School Students’ Character - Yohanes Aris Sri Sadono; Iim Wasliman, (Journal of Science and Education (JSE), 2025)
This study aims to explore value-based scout management in shaping students’ character at the elementary school level. Using a qualitative approach with a case study design, the research was conducted at SDN Kalideres 04, West Jakarta, and SDN Tangerang 14. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using Miles and Huberman’s interactive model. The findings indicate that scout management involving value-oriented planning, organizing, implementation, and supervision effectively supports character development among students. Values such as responsibility, cooperation, discipline, and leadership were successfully internalized through contextual and reflective activities. However, challenges remain in documentation practices, teacher coordination, and evaluation systems. The study recommends strengthening value-based management systems so that scouting can serve as a strategic instrument for character education in elementary schools.